Empirical Antibiotic Prescribing in Adult COVID-19 Inpatients over Two Years in Mexico - Efrén Murillo-Zamora; Xóchitl Trujillo; Miguel Huerta; Oliver Mendoza-Cano; José Guzmán-Esquivel; José Alejandro Guzmán-Solórzano; María Regina Ochoa-Castro; Alan Gabriel Ortega-Macías; Andrea Lizeth Zepeda-Anaya; Valeria Ruiz-Montes de Oca; Mónica Ríos-Silva; Agustin Lugo-Radillo (MDPI AG, 2022)
Background and Objectives: Empirical antibiotic prescribing in patients with coronavirus disease 2019 (COVID-19) has been common even though bacterial coinfections are infrequent. The overuse of antibacterial agents may accelerate the antibiotic resistance crisis. We aimed to evaluate factors predicting empirical antibiotic prescribing to adult COVID-19 inpatients over 2 years (March 2020-February 2021) in Mexico. Materials and Methods: A cross-sectional analysis of a nationwide cohort study was conducted. Hospitalized adults due to laboratory-confirmed COVID-19 were included (n = 214,171). Odds ratios (OR) and 95% confidence intervals (CI), computed by using logistic regression models, were used to evaluate factors predicting empirical antibiotic prescribing. Results: The overall frequency of antibiotic usage was 25.3%. In multiple analysis, the highest risk of antibiotic prescription was documented among patients with pneumonia at hospital admission (OR = 2.20, 95% CI 2.16-2.25). Male patients, those with chronic comorbidities (namely obesity and chronic kidney disease) and longer interval days from symptoms onset to healthcare seeking, were also more likely to receive these drugs. We also documented that, per each elapsed week during the study period, the odds of receiving antibiotic therapy decreased by about 2% (OR = 0.98, 95% CI 0.97-0.99). Conclusion: Our study identified COVID-19 populations at increased risk of receiving empirical antibiotic therapy during the first two years of the pandemic.